2017
DOI: 10.1097/mjt.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Injection With or Without Steroid in Managing Chronic Low-Back and Lower Extremity Pain: A Meta-Analysis of 10 Randomized Controlled Trials

Abstract: Chronic low-back and lower extremity pain is mainly caused by lumbar disc herniation and radiculitis. Various surgery and nonsurgical modalities, including epidural injections, have been used to treat lumbar disc herniation or radiculitis. Therefore, we conducted this meta-analysis to assess the effects of the 2 interventions in managing various chronic low and lower extremity pain. A systematic literature search was conducted to identify randomized controlled trials, which compared the effect of local anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 71 publications
1
19
0
1
Order By: Relevance
“…A meta-analysis (11) stated that epidural injections with only local anesthetics obtained comparable clinical benefits to those with mixture of local anesthetics and steroids. Some studies have reported that local anesthetics and steroids are equally effective in pain control and functional improvements in patients with low back pain or stenosis, and that it is not necessary to use epidural injections of steroids in such cases (10,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A meta-analysis (11) stated that epidural injections with only local anesthetics obtained comparable clinical benefits to those with mixture of local anesthetics and steroids. Some studies have reported that local anesthetics and steroids are equally effective in pain control and functional improvements in patients with low back pain or stenosis, and that it is not necessary to use epidural injections of steroids in such cases (10,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…The local anesthetics are thought to have analgesic effects during the process of injection, which is beneficial for patients to relax. In these days, some researches 46 48 show that ESIs combined with local anesthetics get a better effect on pain relief and functional level in managing chronic low back pain. Therefore, it is necessary to add the local anesthetic during the injections.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar epidural injections can be applied as isolated local anaesthetics, local steroid applications, or combined local anaesthetic and steroid applications [13]. Although there are studies in the literature related to the efficacy of these applications, it has been reported that the combined application of local anaesthetic and steroids is superior to the application of isolated local anaesthetic [14]. In the current study, the combination of local anaesthetic and steroids was used.…”
Section: Discussionmentioning
confidence: 99%